2019
DOI: 10.1055/s-0039-1681100
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of First-Time Venous Thromboembolism in Men and Women

Abstract: Background The relationship between alcohol intake and risk of venous thromboembolism (VTE) is unclear. Men and women differ in their drinking habits, which may affect a possible association. Objective This article investigates the association between alcohol consumption, alcohol dependence and VTE in the total population as well as in men and women separately. Methods We performed a prospective, population-based cohort study in northern Sweden. Study participants were 108,025 (51% wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…However, a borderline significant association between alcohol consumption and VTE risk was observed in women. Sensitivity analysis indicated that the pooled risk estimate became statistically significant when the study by Johansson et al (25), based on men, was removed. These results implied a potential protective role of alcohol (in moderation) against VTE in women.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, a borderline significant association between alcohol consumption and VTE risk was observed in women. Sensitivity analysis indicated that the pooled risk estimate became statistically significant when the study by Johansson et al (25), based on men, was removed. These results implied a potential protective role of alcohol (in moderation) against VTE in women.…”
Section: Discussionmentioning
confidence: 95%
“…The impact of each included study on the summary RR was determined by repeating the meta-analysis after omitting each study in turn. The results indicated that the pooled risk estimate became statistically significant when the study by Johansson et al (25) no significant association was observed in any subgroups, a borderline significant association between alcohol consumption and VTE risk was observed in women [RR, 0.91 (95% CI, 0.82-1.00)] ( Table 2).…”
Section: Highest Vs Lowest Analysismentioning
confidence: 96%
See 3 more Smart Citations